2021
DOI: 10.1002/mabi.202000413
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Study of the Effects of Cationic Liposomes on Delivery across 3D Skin Tissue and Whitening Effects in Pigmented 3D Skin

Abstract: Charged phospholipids are employed to formulate liposomes with different surface charges to enhance the permeation of active ingredients through epidermal layers. Although 3D skin tissue is widely employed as an alternative to permeation studies using animal skin, only a small number of studies have compared the difference between these skin models. Liposomal delivery strategies are investigated herein, through 3D skin tissue based on their surface charges. Cationic, anionic, and neutral liposomes are formulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…In previous studies, formulations of drugs and bioactive molecules within both cationic and anionic liposomes have shown greatly enhanced skin penetration by several times compared to naked molecules via different mechanisms [ 22 , 23 ]. In particular, anionic liposomes below 150 nm penetrated through skin tissues easily and delivered their cargos into deep skin layers [ 13 , 24 , 25 ]. In this study, we successfully prepared anionic SL liposomes with sizes below 200 nm, which might allow for the preferred skin penetration and delivery of Rg3(S).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, formulations of drugs and bioactive molecules within both cationic and anionic liposomes have shown greatly enhanced skin penetration by several times compared to naked molecules via different mechanisms [ 22 , 23 ]. In particular, anionic liposomes below 150 nm penetrated through skin tissues easily and delivered their cargos into deep skin layers [ 13 , 24 , 25 ]. In this study, we successfully prepared anionic SL liposomes with sizes below 200 nm, which might allow for the preferred skin penetration and delivery of Rg3(S).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, a natural combination of phospholipids, such as soybean lecithin (SL), which mainly comprises phosphatidylcholine, phosphatidylinositol, and phosphatidylethanolamine, has been widely investigated for lipid-based formulations owing to its eco-friendly processes, availability for large-scale production, and relatively low cost [ 11 , 12 ]. Several SL-based formulations have been clinically approved by the United States Food and Drug Administration for transdermal delivery of bioactive molecules [ 12 , 13 ]. Accordingly, SL-based liposomes have received attention in the cosmetics industry as practical carriers for the transdermal delivery of active molecules for anti-aging of skin.…”
Section: Introductionmentioning
confidence: 99%
“…We previously observed that cationic liposomes significantly enhanced the percutaneous delivery of niacinamide when they were tested in a 3-D skin system, rather than in a diffusion cell system employing a synthetic membrane. 7 Unlike synthetic skin, 3-D skin possesses pivotal components that can electrostatically interact with cationic liposomes; in particular, keratin in the stratum corneum layers appears to interact with the cationic liposomes to enhance the percutaneous transport of the cationic liposomes as well as niacinamide through the outermost layers of the skin. Therefore, the observed improvements in the clinical indices for the appearance of the skin of the participants can be attributed to the cationic liposomes promoting enhanced percutaneous delivery of niacinamide to the targeted skin cells.…”
Section: Discussionmentioning
confidence: 99%
“…5c). 84,92 Cationic lipids are preferred in liposome formulations for the delivery of nucleic acids. The positive charge on the surface develops electrostatic interaction with negatively charged nucleic acids, improving the encapsulation efficiency (Fig.…”
Section: Composition and Characteristics Of Lnpsmentioning
confidence: 99%